RESEARCH OF OSTEOINTEGRATION OF BICORTICALY FIXED IN SMALL DIAMETER IMPLANTS BY METHOD OF RESONANCE FREQUENCY ANALYSIS - I.V. Pavlish; V.M. Dvornyk (Ukrainian Medical Stomatological Academy, 2017)
The question of application of low-invasive technics of dental implantation appears especially topical at the terms of deficiency of bone tissue. One of going near the decision of this problem, in particular in the lateral departments of lower jaw, there are bicortically fixed in small diameter implants around mandibular nerve. An achievement and maintenance of stability of implants are determined by the condition of successful clinical result of implantation. The aim of this research is to study osteointegration of bicortically fixed in small diameter implants in the lateral areas of lower jaw at the terms of bone tissue deficiency by measuring of their stability with the method of resonance frequency analysis. In our research Osstel ISQ device productions made in Switzerland, that answers the requirements of standards of EN 60601-1 and ISO 9686 and 15223 was used. The group of 16 patients with the complete and partial loss of teeth on a lower jaw with the deficient of bone tissue in lateral departments aged from 34 to 72 was investigated. 98 Art Implants of Simplex line (Ukraine) with the sizes of endoosseal part in 2,8 mm of diameter and 10-14 mm of length was set. All implants were set bicorticaly around lower alveolar nerve with usage the surgical template made by original methodology. Measuring of Implant Stability Quotient (ISQ) was conducted directly after insertion to the implant, after 3 months and 1 year. The dynamics of ISQ depending on primary implant stability were divided into three groups. Conclusions. Determination of ISQ by the method of resonance frequency analysis is an objective index that represents the process of osteointegration of bicortically fixed implants in the lateral departments of lower jaw at the terms deficient of bone tissue. The dynamics of ISQ index change during integration in implants with different primary stability is variable. During integration there is a gradual and more substantial increase of middle ISQ index in implants with low primary stability includes 33,1%. In implants with middle primary stability the ISQ index increases to 17,4% during first-year. In implants with high primary stability there is reduce of middle ISQ index in 3 months on 8,7% by its next increase on 12,2%. Extremely dangerous for integration of implant with immediate loading is possible to count the ISQ index less than 33%.